PENGARUH MODEL PEMBELAJARAN PENEMUAN TERBIMBING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PADA MATERI TEOREMA PYTHAGORAS - Nurcahyati, Elis; Mirza, Ade; Munaldus, Munaldus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the effect of guided discovery learning model assisted by student’s worksheet on mathematical conceptual understanding in pythagorean theorem. This research method was pre-experimental and research design was One Shot Case Study. The subject of this research was students of 8th grade of SMP Negeri 1 Suti Semarang, Bengkayang. The sample of this research was VIII A which amounted to 30 people. The data collected were analyzed using One Sample T tets (α = 5%). Based on data analysis result, obtained t . The result of data analysis using One Sample T test showed that there was no positive effect on mathematical conceptual understanding ability that have been given by guided discovery learning model assited by student worksheet. The conclusion was guided discovery learning model assisted by student worksheet couldn’t be used to increase students’ mathematical conceptual understanding ability in students of 8th grade of SMP Negeri 1 Suti Semarang, Bengkayang.Keywords: Guided Discovery Learning, Mathematical Conceptual Understanding, Pythagorean Theorem, Student Worksheet